2003
DOI: 10.1172/jci200318509
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo analysis of human memory CD4 T cells specific for hepatitis C virus using MHC class II tetramers

Abstract: Containment of hepatitis C virus (HCV) and other chronic human viral infections is associated with persistence of virus-specific CD4 T cells, but ex vivo characterization of circulating CD4 T cells has not been achieved. To further define the phenotype and function of these cells, we developed a novel approach for the generation of tetrameric forms of MHC class II/peptide complexes that is based on the cellular peptide-exchange mechanism. HLA-DR molecules were expressed as precursors with a covalently linked C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
186
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(197 citation statements)
references
References 38 publications
7
186
1
3
Order By: Relevance
“…26 Here, a set of three tetramers containing NS3/4-derived peptides and a single class II molecule (DRB1*0401) were used to study small groups of PCRϩ and PCRϪ individuals. While tetramer-positive cells were detectable in those with resolved infection, no responses were detectable in four individuals with persistent viremia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Here, a set of three tetramers containing NS3/4-derived peptides and a single class II molecule (DRB1*0401) were used to study small groups of PCRϩ and PCRϪ individuals. While tetramer-positive cells were detectable in those with resolved infection, no responses were detectable in four individuals with persistent viremia.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have observed that HCV-specific memory populations are typically CD62L-and CCR7-high (i.e., they have features of "central" memory T cells). 26 While examination of phenotype is theoretically possible using flow cytometricbased cytokine assays, even short-term stimulation can markedly modify the surface expression of CD62L and CCR7 (data not shown), making them unsuitable for this purpose. Thus, we have little current data on the status of the antigen-specific T cells in PCRϩ patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melan-Aspecific cells as shown here), both tissue compartmentalization and self tolerance effects will serve to reduce the frequencies of these populations in the blood, so that ultra-sensitive techniques such as that shown here might be necessary. Finally, the technique can be readily applied to the study of other lymphocyte subsets present at low frequencies as e.g., antigen-specific CD4 + T helper cells by using MHC class II tetramers [19] and NKT cells by using CD1d tetramers, as recently published [20].…”
Section: Discussionmentioning
confidence: 99%
“…100 While reliable protocols exist for the synthesis of pMHC class I multimers, pMHC class II multimers are more difficult to produce and are less promising for direct ex vivo detection of antigenspecific CD4 ϩ T cells, due to the low signal to background noise ratio obtained. However, for viral systems it has been reported that pMHC class II multimers can reveal Ag-specific CD4 ϩ T cells in nonpreselected PBMC, 101,102 and differentiate between CD4 ϩ Tcell clones with high and low TCR avidities. 103 While multimers reveal overall numbers of specific T cells, they can be combined with other assays in order to obtain insights into the phenotypic and functional properties of multimer-binding T cells.…”
Section: Immune Monitoringmentioning
confidence: 99%